Deformation and pressure propagation in deep somatic tissue during painful cuff algometry. (23rd February 2015) - Manafi‐Khanian, B.; Arendt‐Nielsen, L.; Frøkjær, J.B.; Graven‐Nielsen, T.
Abstract Background Cuff algometry is used for quantitative pain assessment although it is not clarified which tissues are actually challenged by the stimulation. This study investigated the mechanical stress and strain distribution in superficial and deep tissues during cuff algometry applied on the lower leg at three different intensities (mild pressure, pain threshold and supra pain threshold). Methods A computational three‐dimensional finite element model of the lower leg with three different layers of soft tissue was developed based on magnetic resonance imaging (MRI) recorded during cuff stimulation. Tissue indentation maps were extracted from the MRI scans and transferred into the model as displacement of boundary condition. In all stimulation conditions, the mean stress of subcutaneous adipose and muscle tissue below the cuff decreased compared with the skin while the mean strain peaked in subcutaneous adipose and decreased in other tissues. Results At pain threshold stimulation intensity, the mean muscle stress was 2.9% of mean skin stress and the mean muscle strain was 55.1% of mean strain in adipose layer. The mean stress and strain increased by 30.4% and 27.1%, respectively, in muscle tissue from painful to supra pain threshold stimulation. The stress and strain was mainly focused around the bones and superficially under cuff. Conclusions This study shows the better capability of cuff algometry for stimulation of deep somatic tissue in terms of generation of mechanical stress and strain in contrast to the more superficial muscle tissue previously demonstrated to be strained by single‐point pressure algometry.